2019
DOI: 10.5585/remark.v18i2.3882
|View full text |Cite
|
Sign up to set email alerts
|

A segmentação geográfica é adequada para estudos de marketing? Uma investigação aplicada ao Brasil

Abstract: Objetivo: Esta pesquisa investiga se a segmentao geogrfica suficiente para avaliar especificidades culturais nas unidades federativas (UF) do Brasil.Mtodo: Considerando valores humanos e axiomas sociais, as UFs foram agrupadas a fim de verificar a similaridade destes agrupamentos com as regies geopolticas oficiais da estrutura do pas. Foi realizado um survey online (N=1.385), utilizando uma amostra no probabilstica. A anlise foi feita a partir de escalonamento multidimencional (MDS), utilizando as dimenses de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 26 publications
(41 reference statements)
2
2
0
Order By: Relevance
“…showed the same pattern across US states: those that are geographically close tend to be close on a two-dimensional cultural map of the US. Alfinito et al (2019) reported a similar pattern for the Brazilian states. Van de Vliert (2020) showed that a correlation between culture and latitude exists also across ethnic groups from the Standard Cross-Cultural Sample, which means that they, too, yield a geographic pattern.…”
Section: Empirical Criteria For Defining Cultural Unitssupporting
confidence: 63%
See 3 more Smart Citations
“…showed the same pattern across US states: those that are geographically close tend to be close on a two-dimensional cultural map of the US. Alfinito et al (2019) reported a similar pattern for the Brazilian states. Van de Vliert (2020) showed that a correlation between culture and latitude exists also across ethnic groups from the Standard Cross-Cultural Sample, which means that they, too, yield a geographic pattern.…”
Section: Empirical Criteria For Defining Cultural Unitssupporting
confidence: 63%
“…Minkov and Kaasa (2021) showed the same pattern across US states: those that are geographically close tend to be close on a two-dimensional cultural map of the US. Alfinito et al. (2019) reported a similar pattern for the Brazilian states.…”
Section: What Is a Cultural Unit?supporting
confidence: 63%
See 2 more Smart Citations